The role of servant leadership practices in human resource excellence: A case study in Algeria - Taouti, Ahmed; Rebiai, Elhachemi; Salhi, Abdelghani; Boudouya, Ismail (International journal of economic perspectives, 2024)
This study aims to determine the role of servant leadership on human resource excellence through a case study of some organizations by distributing a questionnaire to a sample of 87 workers. The study found that there is a high level of servant leadership among workers, and this is due to the interest of the studied organizations in such behavioral practices among workers. There is a high level of excellence in human resources in the organization. There are no statistically significant differences in the study in the responses of the study sample on the level of servant leadership practices and excellence in human resources in the two study organizations due to gender, age, or nature of the organization. It was found that there is a statistically significant correlation between servant leadership (with its dimensions: Empowerment, Emotional processing, social responsibility, Individual development, Humility) and human resource excellence.